Pricing risk and ambiguity: The effect of perspective taking - Stefan T. Trautmann; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2011)
There is a large literature showing that willingness-to-accept (WTA) is usually much higher than willingness-to-pay (WTP) in empirical studies although they should be roughly equal according to traditional economic theory. A second stream of literature shows that people are typically ambiguity averse, i.e. they prefer lotteries with known probabilities over lotteries with unknown ones. Our study combines both streams of literature and analyzes whether there is an interaction between the WTP-WTA disparity and ambiguity aversion.
Keywords: C91; D81; 330; WTP-WTA disparity; ambiguity aversion; comparative ignorance; Willingness to pay; Entscheidung bei Unsicherheit; Risikoaversion; Prospect Theory; Test